Critical wind speed of iced hangers wake vibration based on wind tunnel experiment - Pan Guo; Chao-yu Yang; Zi-kang Tan; Si-yuan Chang; Sheng-li Li; Duo-chang Ren (Advances in Bridge Engineering)
Abstract An iced suspension bridge hanger has an altered aerodynamic shape, potentially causing various types of wind-induced vibrations. A wind tunnel experiment was performed, based on the DenHartog galloping theory, to study the wake galloping of the iced suspension bridge hangers at different hanger spacings. The results revealed that, for iced pin joint hangers, the pneumatic characteristics of the leeward hanger are more stable when the hanger spacing is in the 4.8D ≤ L ≤ 6.2D range. The range of wind attack angle corresponding to the negative value of the DenHartog coefficient increased gradually with the increase in hanger spacing. For iced straddling hangers, the effect of lift must be considered when the static wind load of iced straddling hangers is calculated. The DenHartog coefficients of iced hangers under different hanger spacings all exceeded the -1.0 specified in the code for Wind Resistance Design of Highway Bridges (JTG/T3360-01–2018). The aerodynamic characteristics of iced leeward hangers were more stable when the hanger spacing was A × B = 8D × 4D. Therefore, measures should be taken to increase the rigid vibration-damping frame and improve the critical wind speed of the hangers to avoid vibration in iced hangers.